Assessing Healthcare Facility Accessibility Using Isochrone and Geometry Methods in Mojokerto Regency: A Public Health Perspective - Suprayogi, Dedy; Nugroho, Bayu Adhi (Journal of Health Science and Prevention, 2025)
The use of spatial methods for geographic modeling grew due to various advantages, especially simplicity and convenience. In the health sector, spatial analysis was valuable in measuring the accessibility of healthcare facilities in the community. Mojokerto Regency, a district/city in East Java, excelled in the health sector but still had the potential for further improvement, particularly in access to healthcare facilities. This research aimed to analyze the affordability of healthcare facilities, including hospitals, health centers, medical laboratories, and pharmacies in Mojokerto District. The method used in the research was isochrone and geometry with QGIS software and the Travel Time plugin. The data processed was taken from the local government and the Mojokerto Regency map in 2023. The research results showed that the affordability of pharmacy access by bike had the highest coverage at 88.9%, followed by car access to community health centers at 85.8%. In contrast, walking had low coverage, only 24.1%. Based on the evidence, pharmacies and health centers were abundant in most areas, but there were few health laboratories. Therefore, to maximize public access to healthcare facilities, the government needed to improve non-private transportation infrastructure and expand public transportation options. In addition, strategic planning for the equal distribution of health laboratories and pharmacies was urgently required to reduce disparities and ensure better health service coverage.